2019
DOI: 10.1016/j.heliyon.2019.e02501
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of ubiquitous harmful microbial lineages in water using an innovative Zn2Ti0.8Fe0.2O4 nanostructure: dielectric and terahertz properties

Abstract: Many ubiquitous dangerous microbial lines could originate in different sources of polluted water and be distributed to tap water, which could cause multiple types of illnesses to humans and livestock. Despite enormous attempts to guarantee safety of potable water, these species are still regarded to be threated prevalent health issues and concerns. However, these species need a powerful disinfectant to be removed from contaminated water for receiving clean and healthy water. This study was therefore conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…It is well‐known that chlorine can prevent the growth of biofilm in water systems. The microorganisms, which are exposed to chlorine, are formed during the stages of water treatment (El Nahrawy, Hammad, Bakr, Hemdan, & Wassel, 2019; Hammad et al., 2020). A few of the previous studies relating to the interaction between pipe materials at low chlorine rates and microbial diversity (<1.0 mg/L chlorine) received adequate details (Hemdan & Elliethy, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…It is well‐known that chlorine can prevent the growth of biofilm in water systems. The microorganisms, which are exposed to chlorine, are formed during the stages of water treatment (El Nahrawy, Hammad, Bakr, Hemdan, & Wassel, 2019; Hammad et al., 2020). A few of the previous studies relating to the interaction between pipe materials at low chlorine rates and microbial diversity (<1.0 mg/L chlorine) received adequate details (Hemdan & Elliethy, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…From a stock solution of each tested compound (50 mg/mL), three different concentrations (2.5, 5, and 10 mg/mL) of each compound were transferred to a tube containing 20 µL of fresh pathogen microbial culture to estimate the lethal concentrations. After three different time intervals (5,10,15, and 20 min), the densities of surviving cells were counted using the plate count viability assay [75].…”
Section: Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%
“… where k 1 (1 min −1 ) is the rate of inactivation; q e (mg·g −1 ), and q t (mg·g −1 ) are the amounts adsorbed at equilibrium and at time t (min), respectively. A straight line of ln ( q e − q t ) versus t suggested that this kinetic model was applied to the data [ 38 ].…”
Section: Methodsmentioning
confidence: 99%